(x-1) (x.x+7) = (x-1) (5x+1)
Resposta: {1,2,3}
Soluções para a tarefa
Respondido por
0
(x-1) (x.x+7) = (x-1) (5x+1)
x.x + 7 = 5x + 1 ==> x² - 5x + 1 - 7 = 0
x² - 5x - 6 = 0
Δ = (-5)² - 4.1.(-6) ==> 25 - 24 = 1
x= 5 +/- 1
2
x1 = 5+1 ==> x1= 3 ; x2 = 5 - 1 ==> x2 = 2
2 2
==============================================
x- 1 = 0 ==> x = 1
Perguntas interessantes
História,
1 ano atrás
Pedagogia,
1 ano atrás
Português,
1 ano atrás
Física,
1 ano atrás
Contabilidade,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás